SIMULATION STUDIES ON STRUCTURE VIBRATION OF GEARBOX-BASE COUPLING SYSTEM BASED ON THE SUBSTRUCTURE METHOD - WEI YanMing; ZHANG XueYan; YUE YiDan; ZHANG JiaJia (Jixie qiangdu)
In order to raise the efficiency of the structure vibration simulation of gearbox-base coupling system,the equivalent mass and stiffness of the base on each connection point was extracted using substructure method,and the base was equivalent to some mass elements and spring elements. Based on this,the structure vibration simulation model of the gearbox-base coupling system was established and the structure vibration simulation was completed. The simulation results were compared with the simulation results using the full finite element method. The results show the difference between the equivalent acceleration levels on each connection point obtained by using the substructure method and that obtained by using the full finite element method does not exceed 3 dB,and the simulation time of the substructure method only accounts for 38. 5% of that of the full finite element method.